'Journey in the world of professions and work': A career intervention for children. Issue 5 (3rd September 2018) - Ginevra, Maria Cristina; Nota, Laura
Abstract: A structured ten-unit training was devised to stimulate some career adaptability resources such as optimism and hope toward the future, curiosity, career exploration, and occupational knowledge in children. Ten classes, for a total of 154 children (79 boys and 75 girls) with a mean age of 10.65 years (SD = 1.24), were randomly assigned to either the experimental, who was the focus of the intervention, or control group. At post-test the experimental group held significantly more hope, optimism, curiosity, career exploration, occupational knowledge, information, planning, and time perspective than the control group. The pattern of effect sizes strengthens the idea that the training enhanced experimental participants' some career adaptability resources.